2019
DOI: 10.4274/eajem.galenos.2019.85047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hemodialysis and Hemoperfusion in Poisoned Patients

Abstract: Aim:The aim of our study was to evaluate the demographic data, type of toxic substance, Glasgow Coma scale (GCS), Poisoning Severity score (PSS) and the prognosis of the patients who were admitted to the emergency department (ED) with a preliminary diagnosis of acute intoxication and then underwent hemodialysis (HD) or hemoperfusion (HP), and to compare this data with other studies. Materials and Methods:The study retrospectively analyzed the files of 36 poisoned patients who were admitted to the ED and who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Thus, patients exposed to pesticides may, from the dialysis process, have eliminated possible residues and toxins that may have remained in the body during exposure. Research has shown that the procedures currently used in nephrology may soon also be used more widely for the detoxification process of patients poisoned by pesticides 42 . This fact constitutes a probable argument for the lack of statistical difference between the laboratory tests of exposed and non-exposed patients in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients exposed to pesticides may, from the dialysis process, have eliminated possible residues and toxins that may have remained in the body during exposure. Research has shown that the procedures currently used in nephrology may soon also be used more widely for the detoxification process of patients poisoned by pesticides 42 . This fact constitutes a probable argument for the lack of statistical difference between the laboratory tests of exposed and non-exposed patients in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Desse modo, pacientes expostos a agrotóxicos podem, a partir do processo dialítico, ter eliminado os possíveis resíduos e toxinas que porventura tenham permanecido no organismo durante a exposição. A pesquisa mostrou que os procedimentos, atualmente utilizados na nefrologia, podem, em breve, também ser utilizados de forma mais ampla para o processo de desintoxicação de pacientes envenenados por agrotóxicos 42 . Esse fato constitui-se um provável argumento do não aparecimento de diferença estatística entre os exames laboratoriais dos pacientes expostos e não expostos na presente pesquisa.…”
Section: Discussionunclassified
“…However, when toxins are evaluated, methanol poisoning in adult patients and salicylate poisoning in pediatric patients are more prominent. Therefore, impaired consciousness and treatment-resistant metabolic acidosis are among the vital HD indications in adult poisoning patients [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mortality rate in our study seems to be high according to this report, it was found to be lower when compared to studies that included only critical poisoning patients who underwent HD. In a study that included 36 poisoning patients and used HD or HP as extracorporeal treatment, the mortality rate was 30.6%, while it was 27.3% in another similar study [16,17]. The most common reason for admission was impaired consciousness when all patients were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation